2022
DOI: 10.1007/s44199-022-00047-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rain-Fed Conditions on Yield of Mash Bean Genepool by Using Augmented Design

Abstract: The augmented block design (ABD) is commonly used in breeding programs to evaluate the performance of large number of genotypes using non-replicated new test treatments and replicated check treatments. The purpose of this design is to determine which test treatment performs better than check treatments. The objective of this study is to identifying better genotype of Mash been than check treatment under rain feed condition of Pakistan. For this purpose, the data of 125 mash been genotypes included 5 check entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…These traits have been reported to be of great pertinence for the selection and establishment of breeding criteria to increase the grain yield of legumes. These findings are in accordance with a previous study, where it was reported that the determination of pod numbers per plant and thousand grain weight were the most crucial strategies for projecting the grain yield, because these were linearly associated with the grain yield of legumes [63,64]. Contrastingly, a greater number of pods per plant contained a lower number of grains per pod, and thus this was negatively associated with the thousand grain weight of black gram.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These traits have been reported to be of great pertinence for the selection and establishment of breeding criteria to increase the grain yield of legumes. These findings are in accordance with a previous study, where it was reported that the determination of pod numbers per plant and thousand grain weight were the most crucial strategies for projecting the grain yield, because these were linearly associated with the grain yield of legumes [63,64]. Contrastingly, a greater number of pods per plant contained a lower number of grains per pod, and thus this was negatively associated with the thousand grain weight of black gram.…”
Section: Discussionsupporting
confidence: 92%
“…PC analysis can identify the traits that account for variation in crop yields [64][65][66][67][68][69], and thus, it may be employed for confirming the most influential response variables [70][71][72]. According to the PC1/PC2 combination analysis in this study, the unamended control treatment remained the least affected compared with the amended treatments for both cultivars of black gram.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with our results since the trait with the highest number of QTLs was 100-seed weight (100SW) followed by pod harvest index (PHI), which have a positive correlation with the following traits: pods per plant and seed per pod [ 68 , 69 ]. However, a negative correlation between pods per plant and 100-seed weight (100SW) was recently reported in common bean, suggesting that a high number of pods per plant reduces seed weight [ 70 ].…”
Section: Discussionmentioning
confidence: 99%